Analisis Komparasi Efektivitas Penjualan Sebelum Dan Sesudah Menggunakan Video Marketing Online Talk Fusion Di Manado - Tandusan, Chevy F (Universitas Sam Ratulangi, 2015)
conventional manners of marketing systems that are considered inefficient and ineffective has been replaced by internet marketing which is easier to use, has a wider range of consumers, and provides better result. Social media has started to be used as a growing medium for the promotion of business activities because it has an attractive appearance. This study is conducted to see whether there are differences in effectiveness of sales before and after the usage of Talk Fusion online marketing videos in Manado. The analysis method in this study is comparative research by using paired samples t-test. This study uses 30 respondents who are obtained by using snowball and purposive sampling. The result of this study shows that there are significant differences in the effectiveness of sales before and after the usage of Talk Fusion online marketing videos in Manado. Keywords: sales effectiveness, internet marketing, online marketing videos